Knowledge, attitude, and practice of atrial fibrillation in high altitude areas - Li, Ke; Liu, Jinfeng; Zhu, Yan (Frontiers in Public Health, 2024)
Background To investigate the knowledge, attitude, and practice (KAP) of atrial fibrillation (AF) among the general population in high-altitude areas. Methodology A web-based cross-sectional study was conducted among the general population in high-altitude areas. Results A total of 786 valid questionnaires were enrolled, with a mean age of 34.75 ± 14.16 years. The mean score of knowledge, attitude and practice were 8.22 ± 6.50 (possible range: 0–10), 28.90 ± 5.63 (possible range: 8–40), 34.34 ± 6.44 (possible range: 9–45), respectively. The multivariate analysis showed that knowledge scores (OR = 1.108, 95% CI = 1.075–1.142, p < 0.001), attitude scores (OR = 1.118, 95% CI = 1.081–1.156, p < 0.001), and never smoking (OR = 2.438, 95% CI = 1.426–4.167, p = 0.001) were independently associated with proactive practice. The structural equation modeling (SEM) showed direct effect of knowledge on practice (p = 0.014), and attitude on practice (p = 0.004), while no effect of knowledge on attitude (p = 0.190). Conclusion The general population in high-altitude regions had adequate knowledge, positive attitude, and proactive practice towards AF. The SEM was suitable for explaining general population’ KAP regarding AF, revealing that knowledge directly and positively affected attitude and practice.